Macro-financial models of Canadian dollar interest rate swap yields. - Tanweer Akram; Khawaja Mamun (PLoS ONE)
This paper analyzes the dynamics of Canadian dollar-denominated (CAD) interest rate swap yields. It applies autoregressive distributive lag (ARDL) models, using monthly time series data, to estimate the effects of the current short-term interest rate on interest rate swap yields after controlling for relevant macro-financial variables. It shows that the current short-term interest rate is a crucial driver of the CAD swap yields of different maturity tenors. Previous empirical research testing the Keynesian hypothesis, which maintains that the current short-term interest rate has a decisive influence on the long-term interest rate, has discerned similar patterns for interest rate swaps denominated in other currencies. Thus, the findings of this paper lend additional support to the Keynesian hypothesis by showing that the same pattern holds for CAD interest rate swap yields.